Fluid control valve and method of manufacturing same
By using fluoride resin and carbon-based additives in the film members of the liquid control valve and forming conductive welding areas on the backside, the problems of electrostatic accumulation and film member strength reduction when controlling the liquid flow are solved, and higher electrolytic stability and film member strength are achieved.
Patent Information
- Application Number
- JP2022084617
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-05-24
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2042-05-24
AI Technical Summary
Existing liquid control valves are prone to static electricity when controlling liquid flow, causing liquid and wet parts to be charged, increasing the risk of electrolytic damage, and during laser welding, the strength of the film members may be reduced, increasing the risk of fatigue damage.
A liquid control valve made of a carbon-based additive dispersed in the fluoride resin is used to form a conductive welding area on the back side of the film members, reducing the heat influence during laser welding and increasing the strength of the film members.
It effectively prevents the accumulation of static electricity in the control liquid and the wet part, reduces the risk of electrolytic damage, and by reducing the influence of heat, the strength of the film members is improved, and liquid leakage caused by fatigue damage is avoided.
Smart Images

Figure 0007655884000001 
Figure 0007655884000002 
Figure 0007655884000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a fluid control valve including a flow path through which a control fluid flows, an annular valve seat provided in the flow path, a diaphragm member that controls the flow of the control fluid by moving toward and away from the annular valve seat, and a drive shaft that is coaxially arranged with the annular valve seat and drives the diaphragm member in the direction of moving toward and away from the annular valve seat, and a method for manufacturing such a fluid control valve. [Background technology]
[0002] As a fluid control valve that controls the flow of a fluid by abutting or separating a valve body from a valve seat, for example, a chemical valve is used in a semiconductor manufacturing device as a fluid control valve that controls the flow rate of a chemical liquid. In such a fluid control valve, a diaphragm member operated by a drive shaft abuts and separates from an annular valve seat to control the flow of a controlled fluid. As a diaphragm member, for example, as disclosed in Patent Document 1, a diaphragm member formed by joining a thin film member (the diaphragm in Patent Document 1) to a shaft member (the auxiliary shaft in Patent Document 1) that is connected to a drive shaft by laser welding is known. Such a thin film member divides the inside of the fluid control valve into a liquid-contacting portion that comes into contact with the control fluid and a non-liquid-contacting portion that does not come into contact with the control fluid. In addition, the thin film member is repeatedly elastically deformed when the diaphragm member abuts and separates from the annular valve seat. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-29522 [Patent Document 2] JP 2010-121689 A Summary of the Invention [Problem to be solved by the invention]
[0004] (First issue) When the control fluid passes through the flow channel, a positive or negative charge is adsorbed to the inner surface of the flow channel at the interface between the fluid and the inner surface of the flow channel, and a charge of the opposite polarity to the charge adsorbed to the inner surface of the flow channel remains in the fluid. As the control fluid flows, the fluid that was in contact with the inner surface of the flow channel is separated from it, creating an electric field, causing the control fluid and the parts that come into contact with the fluid to become charged. In other words, static electricity is generated.
[0005] When the control fluid and the wetted parts are charged, the potential difference between the wetted parts and non-wetted parts inside the fluid control valve increases. When the potential difference increases, the thin film member is very thin, for example, about 0.2 mm, so there is a possibility of dielectric breakdown. When dielectric breakdown occurs, electric charges move rapidly inside the thin film member, generating heat. This generated heat may cause microcracks to occur in the thin film member at the point where dielectric breakdown occurs. If a crack occurs, there is a risk of fluid leakage. In addition, since the thin film member repeatedly undergoes elastic deformation due to contact with and separation from the valve seat, stress is concentrated at the point where the crack occurs, causing the crack to grow and eventually causing fatigue breakdown. In addition, for example, in semiconductor manufacturing equipment, if the charged control fluid comes into contact with a wafer during development of a circuit pattern, there is a risk of malfunction such as developing a defective circuit pattern.
[0006] As a fluid control valve for preventing dielectric breakdown of a thin-film member, a diaphragm valve disclosed in Patent Document 2 is known. This diaphragm valve is intended to promote the discharge of static electricity by forming a conductive film on the non-liquid-contacting portion of the valve. However, the position where the conductive film is formed is far away from the liquid-contacting portion, and there is concern that this is not effective in preventing charging of the liquid-contacting portion.
[0007] (Second issue) When the shaft member and the thin film member are joined by laser welding, the strength of the thin film member may be reduced due to the influence of heat during welding. FIG. 14 is a cross-sectional view of the vicinity of the boundary between the thin film member 2222 and the shaft member 2221 of a diaphragm member formed by joining the thin film member 2222 and the shaft member 2221 by laser welding. As shown in FIG. 14, a welded portion W21 is formed by laser welding at the boundary between the thin film member 2222 and the shaft member 2221. This welded portion W21 is a portion that is melted and solidified by laser irradiation, that is, a portion that is affected by heat due to laser welding. The range A21 of the thin film member 2222 that is affected by heat is about 80% of the thickness t21 of the thin film member 2222, and is a wide range. In this way, if the range affected by heat is large, there is a concern that the strength of the thin film member 2222 may be reduced. If the strength of the thin film member 2222 is reduced, the risk of fatigue failure increases due to repeated elastic deformation during the contact and separation operation of the diaphragm member.
[0008] The present invention has been made to solve the above problems, and has an object to provide a fluid control valve and a manufacturing method thereof that are capable of preventing the control fluid from becoming electrically charged and also capable of preventing a decrease in strength of the thin film member due to laser welding. [Means for solving the problem]
[0009] In order to solve the above problems, the flow control valve and the method for manufacturing the flow control valve of the present invention have the following configuration. (1) A fluid control valve comprising: a flow path through which a control fluid flows; an annular valve seat provided on the flow path; a diaphragm member that controls the flow of the control fluid by coming into contact with and moving away from the annular valve seat; and a drive shaft that is coaxially arranged with the annular valve seat and drives the diaphragm member in the direction of coming into and moving away from the annular valve seat; the diaphragm member comprises: a shaft member that is connected to an end of the drive shaft on the side of the annular valve seat; a thin film member made of perfluoroalkoxyalkane and positioned in surface contact with an end face of the shaft member opposite to the end connected to the drive shaft; and a welded portion formed by laser welding that joins the shaft member and the thin film member at a boundary between the shaft member and the thin film member; and the shaft member is made of a fluororesin having a carbon-based additive dispersed therein; the shaft member absorbs the laser light when the laser welding is performed, thereby making the area in the thin film member where a weld mark is generated by the laser welding smaller than half the thickness of the thin film member, thereby preventing a decrease in strength of the thin film member; It is characterized by:
[0010] (5) A method for manufacturing a fluid control valve including a flow path through which a control fluid flows, an annular valve seat provided on the flow path, a diaphragm member that controls the flow of the control fluid by contacting and separating from the annular valve seat, and a drive shaft that is coaxially arranged with the annular valve seat and drives the diaphragm member in the direction of contact and separation, the method comprising the steps of: joining a shaft member coupled to an end of the drive shaft on the annular valve seat side, and a thin film member made of perfluoroalkoxyalkane and positioned in surface contact with an end face of the shaft member opposite to the end coupled to the drive shaft, by forming a welded portion at the boundary between the shaft member and the thin film member by laser welding, to obtain the diaphragm member; the shaft member is made of a fluororesin containing a carbon-based additive; the shaft member absorbs the laser light when the laser welding is performed, thereby making the area in the thin film member where a weld mark is generated by the laser welding smaller than half the thickness of the thin film member, thereby preventing a decrease in strength of the thin film member; It is characterized by:
[0011] According to the fluid control valve described in (1) or the manufacturing method of the fluid control valve described in (5), the shaft member is made of a fluororesin having a carbon-based additive dispersed therein, and therefore has higher electrical conductivity than a shaft member made of a general fluororesin. This allows static electricity generated by the passage of the control fluid through the flow path to be discharged, and makes it possible to prevent the control fluid and the liquid-contacting parts from being charged.
[0012] If the control fluid and the wetted parts can be prevented from being charged, the increase in the potential difference between the wetted parts and the non-wetted parts inside the fluid control valve can be prevented. If the increase in the potential difference can be prevented, the occurrence of dielectric breakdown of the thin film member can be prevented. If the occurrence of dielectric breakdown of the thin film member can be prevented, the occurrence of microcracks due to dielectric breakdown can be prevented, and further, the occurrence of fluid leakage and fatigue breakdown caused by the cracks can be prevented. Furthermore, if the control fluid can be prevented from being charged, for example, in a semiconductor manufacturing device, it is possible to prevent the charged control fluid from coming into contact with a wafer, thereby reducing the risk of causing problems such as developing a defective circuit pattern.
[0013] According to the fluid control valve described in (1) or the manufacturing method of the fluid control valve described in (5), the shaft member is made of a fluororesin having a carbon-based additive dispersed therein, and therefore has a higher laser light absorption than a case where the shaft member is made of a general fluororesin. Since the laser light absorption of the shaft member is increased, when the shaft member and the thin film member are joined by laser welding, the shaft member is more likely to absorb laser light, and therefore the joining can be performed with a lower amount of heat than before, and the range of the thin film member that is affected by heat can be made smaller than before. If the range of the thin film member that is affected by heat can be made smaller, it is possible to prevent the strength of the thin film member from being reduced by laser welding. This can reduce the risk of fatigue failure of the thin film member due to repeated elastic deformation.
[0014] (2) In the fluid control valve described in (1), the thin film member has an abutment portion on the surface opposite to the shaft member that abuts against the annular valve seat, and the welded portion is formed at least on the back side of the abutment portion.
[0015] (6) In the method for manufacturing a fluid control valve described in (5), the thin film member has an abutment portion on a surface opposite to the shaft member that abuts against the annular valve seat, and the welded portion is formed at least on a back side of the abutment portion.
[0016] In general, in a fluid control valve, the flow passage area between the annular valve seat and the abutment portion that abuts against the annular valve seat is smaller than the other portions. Therefore, the flow speed of the control fluid is fast when it flows between the annular valve seat and the abutment portion. Therefore, static electricity is easily generated when the control fluid flows between the annular valve seat and the abutment portion.
[0017] According to the fluid control valve described in (2) or the manufacturing method of the fluid control valve described in (6), a welded portion is formed on the back side of the contact portion. In other words, the thin film member is joined to the shaft member having enhanced conductivity on the back side of the contact portion where static electricity is likely to be generated, so that discharge can be performed more reliably.
[0018] (3) In the fluid control valve according to (1) or (2), the thin film member has a layer containing the carbon-based additive on the side facing the shaft member.
[0019] (7) In the method for manufacturing a fluid control valve according to (5) or (6), the thin film member has a layer containing the carbon-based additive on the side facing the shaft member.
[0020] According to the fluid control valve described in (3) or the manufacturing method of a fluid control valve described in (7), the thin film member has a layer containing a carbon-based additive and having enhanced electrical conductivity on the side facing the shaft member. That is, the thin film member has a layer having enhanced electrical conductivity bonded to the shaft member having enhanced electrical conductivity. This makes it possible to more reliably discharge static electricity generated by the passage of the control fluid through the flow path.
[0021] According to the fluid control valve described in (3) or the manufacturing method of the fluid control valve described in (7), the thin film member has a layer containing a carbon-based additive and having enhanced laser light absorbency on the side facing the shaft member. That is, the thin film member has a layer having enhanced laser light absorbency joined to the shaft member having enhanced laser light absorbency. Since the layers of the shaft member and the thin film member facing the shaft member are easily absorbent of laser light, when the shaft member and the thin film member are joined by laser welding, the joining can be performed with a lower amount of heat than in the past, and the area of the thin film member that is affected by heat can be made smaller.
[0022] (4) In the flow control valve according to any one of (1) to (3), it is preferable that the carbon-based additive is, for example, carbon black or carbon nanotubes.
[0023] (8) In the method for producing a flow control valve according to any one of (5) to (7), the carbon-based additive is carbon black or carbon nanotubes.
[0024] When carbon black is used, the content is preferably 1.5% by weight or more and 5% by weight or less, and more preferably 3% by weight or more and 4% by weight or less. If the content is less than 1.5% by weight, sufficient laser light absorption and electrical conductivity cannot be obtained. Also, the higher the content, the higher the laser light absorption and electrical conductivity can be, but if the content exceeds 5% by weight, there is a concern that the material strength may decrease.
[0025] When carbon nanotubes are used, the content is preferably 0.01% by weight or more and 0.1% by weight or less. If the content is less than 0.01% by weight, sufficient laser light absorption and electrical conductivity cannot be obtained. Also, the higher the content, the higher the laser light absorption and electrical conductivity can be, but if the content exceeds 1% by weight, there is a concern that the material strength may decrease. Effect of the Invention
[0026] According to the flow control valve or the method for manufacturing the flow control valve of the present invention, it is possible to prevent the control fluid from being charged, and also possible to prevent a decrease in strength of the thin film member due to laser welding. [Brief description of the drawings]
[0027] [Figure 1] FIG. 2 is a cross-sectional view of the fluid control valve according to the embodiment, illustrating a valve closed state. [Diagram 2] FIG. 2 is a cross-sectional view of the fluid control valve according to the embodiment, illustrating an open state. [Diagram 3] FIG. 4 is a cross-sectional view of a diaphragm member. [Figure 4] FIG. 4 is a partially enlarged view of a portion A in FIG. [Diagram 5] 5(a) to 5(c) are diagrams illustrating a process for manufacturing a diaphragm member by laser welding. [Figure 6] 1 is an image diagram showing the scanning state of an infrared laser as viewed from the light source side in laser welding. FIG. [Figure 7] 7 is a cross-sectional view taken along the line BB in FIG. 6, illustrating a state after laser welding. [Figure 8] FIG. 13 is a diagram showing a modified example of the fluid control valve. [Figure 9] FIG. 13 is a diagram showing a modified example of the fluid control valve. [Figure 10] 13A and 13B are diagrams illustrating modified examples of the diaphragm member. [Figure 11] 11 is a cross-sectional view of a fluid control valve using the diaphragm member shown in FIG. 10. [Figure 12] 13A and 13B are diagrams illustrating other aspects of the welded portion of the diaphragm member. [Figure 13] 13A and 13B are diagrams illustrating other aspects of the welded portion of the diaphragm member. [Figure 14] 1 is a diagram for explaining a problem of a fluid control valve according to a conventional technique. [Figure 15] 1 is a diagram for explaining a problem of a fluid control valve according to a conventional technique. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] (Configuration of the fluid control valve) The configuration of the fluid control valve 1 according to the first embodiment will be described in detail with reference to the drawings. FIG. 1 is a cross-sectional view of the fluid control valve 1 according to the present embodiment, showing a valve closed state. FIG. 2 is a cross-sectional view of the fluid control valve 1 according to the present embodiment, showing a valve open state. FIG. 3 is a cross-sectional view of a diaphragm member 122 used in the fluid control valve 1 according to the present embodiment. FIG. 4 is a partial enlarged view of a portion A in FIG. 3.
[0029] The fluid control valve 1 is an air-operated normally-closed type fluid valve that controls the flow rate of fluid in a semiconductor manufacturing process. The fluid control valve 1 is made up of a drive unit 11 and a valve unit 12, as shown in FIG.
[0030] The driving unit 11 includes a first housing 111 and a second housing 112 stacked on top of the first housing 111, and includes a drive shaft 113 therein. The first housing 111 has a cylindrical shape with an open end (lower end in FIG. 1) on the second housing 112 side and a closed other end (upper end in FIG. 1). A first air supply / exhaust port 111a is formed on the outer circumferential surface of the first housing 111. The open end of the first housing 111 on the second housing 112 side is airtightly fitted into the upper end of the second housing 112 in FIG. 1 via an O-ring 115.
[0031] Second housing 112 has a cylindrical shape with both an end on the first housing 111 side (upper end in FIG. 1) and an end on the valve portion 12 side (lower end in FIG. 1) open. Second air supply / exhaust port 112a is formed on the outer circumferential surface of second housing 112. First housing 111 and second housing 112 are aligned coaxially, and a piston chamber 116 is formed by the hollow portion inside first housing 111 and the hollow portion inside second housing 112.
[0032] A drive shaft 113 is loaded in the piston chamber 116 so as to be slidable in the up-down direction in Fig. 1. Here, the up direction in Fig. 1 is the valve opening direction, and the down direction in Fig. 1 is the valve closing direction. The drive shaft 113 is equipped with a disk-shaped piston portion 113a, which divides the piston chamber 116 into an upper chamber 116a and a lower chamber 116b. An O-ring 117 is disposed between the outer periphery of the piston portion 113a and the inner wall of the piston chamber 116, and keeps the upper chamber 116a and the lower chamber 116b airtight.
[0033] The upper chamber 116a communicates with the first air supply / exhaust port 111a through an air passage 111b, and the lower chamber 116b communicates with the second air supply / exhaust port 112a through an air passage 112b. A coil spring 114 is disposed in the upper chamber 116a. The lower end of the coil spring 114 in FIG. 1 abuts against the upper end surface of the piston portion 113a, and the upper end of the coil spring 114 in FIG. 1 abuts against the upper surface of the upper chamber 116a. Therefore, the drive shaft 113 is biased in the valve closing direction (downward in FIG. 1) by the elastic force of the coil spring 114.
[0034] Furthermore, the drive shaft 113 is provided with a cylindrical first piston rod 113b and a cylindrical second piston rod 113c at the upper and lower ends of the piston portion 113a, respectively.
[0035] The first piston rod 113b is inserted into a groove 111c provided on the underside of the first housing 111 in FIG. 1, and is guided when the drive shaft 113 slides in the vertical direction in FIG.
[0036] The second piston rod 113c is inserted into a through hole 112c that penetrates the lower end surface of the second housing 112 and the lower chamber 116b. An O-ring 118 is disposed between the outer peripheral surface of the second piston rod 113c and the inner peripheral surface of the through hole 112c to keep the lower chamber 116b airtight. A diaphragm member 122 that constitutes the valve unit 12 is screwed to the tip of the second piston rod 113c.
[0037] The valve unit 12 is connected to the lower side of the drive unit 11 in FIG. 1, and is composed of a valve unit main body 121, a diaphragm member 122, and a base 123. The valve unit main body 121 has an input flow path 121a into which a fluid such as a chemical solution is input, and an output flow path 121b from which the input fluid is output. A valve chamber 121c is formed in the center of the upper end surface of the valve unit main body 121 in FIG. 1, and the valve chamber 121c communicates with the input flow path 121a and the output flow path 121b. The input flow path 121a communicates with the output flow path 121b, forming a series of flow paths through which the control fluid flows. An annular valve seat 121d against which the diaphragm member 122 comes into contact and separates is formed on the bottom surface of the valve chamber 121c.
[0038] As shown in FIG. 3, the diaphragm member 122 is a combination of a shaft member 1221 and a thin film member 1222 that abuts against and is spaced from the annular valve seat 121d.
[0039] The shaft member 1221 is formed of PFA (perfluoroalkoxyalkane) in which carbon black is dispersed. The carbon black content is preferably 1.5% by weight or more and 5% by weight or less, and more preferably 3% by weight or more and 4% by weight or less. In this embodiment, the carbon black content is about 3.5% by weight.
[0040] The shaft member 1221 is formed in a substantially cylindrical shape. A threaded portion 1221c is drilled in the end face of the shaft member 1221 on the drive shaft 113 side (the upper end face in FIG. 1). The tip of the drive shaft 113 on the annular valve seat 121d side is screwed into this threaded portion 1221c. As a result, the shaft member 1221 is fixed in a state of being positioned coaxially with the drive shaft 113, and the shaft member 1221 can move up and down as the drive shaft 113 moves up and down. A thin film member 1222 is joined in a surface contact state to the end face of the shaft member 1221 opposite to the drive shaft 113 (the lower end face in FIG. 1).
[0041] The thin film member 1222 is a disk-shaped film formed by injection molding or extrusion molding using PFA as a material. The thickness is not particularly limited, but is, for example, about 0.2 mm. The thin film member 1222 is coaxially positioned and joined to the shaft member 1221. The outer peripheral end of the thin film member 1222 is sandwiched from above and below by the second housing 112 and the valve body 121, as shown in FIG. 1. As a result, the thin film member 1222 is fixed inside the valve chamber 121c, and the valve chamber 121c is divided into a liquid-contacting portion and a non-liquid-contacting portion. The area above the thin film member 1222 (the shaft member 1221 side) is the non-liquid-contacting portion, and the area below the thin film member 1222 (the annular valve seat 121d side) is the liquid-contacting portion. Therefore, the surface of the thin film member 1222 on the annular valve seat 121d side is the liquid-contacting surface 1222a with which the control fluid comes into contact.
[0042] Furthermore, the thin film member 1222 is fixed in the valve chamber 121c, and thus elastically deforms repeatedly as the drive shaft 113 and the shaft member 1221 move up and down. This repetition of elastic deformation causes the liquid contact surface 1222a of the thin film member 1222 to repeatedly come into contact with and separate from the annular valve seat 121d. Of the liquid contact surface 1222a, the portion that comes into contact with and separates from the annular valve seat 121d is referred to as a contact portion 1222b (the portion indicated by the thick dashed line in the figure). Note that the contact portion 1222b is preferably formed by a molded surface. This is to reduce the surface roughness of the contact portion 1222b and prevent dust generation due to the repetition of contact and separation with the annular valve seat 121d.
[0043] The shaft member 1221 and the thin film member 1222 are joined by laser welding, and the boundaries between the shaft member 1221 and the thin film member 1222 form welded parts 32, as shown in Fig. 4. In the diaphragm member 122 in this embodiment, the boundaries between the shaft member 1221 and the thin film member 1222 all form welded parts 32, and the shaft member 1221 and the thin film member 1222 are joined to each other over the entire surface where they come into contact.
[0044] As described above, the shaft member 1221 constituting the diaphragm member 122 is made of PFA with carbon black dispersed therein, and therefore has higher conductivity than that of a general fluororesin. This allows static electricity generated by the passage of the control fluid through the flow path to be discharged, and prevents the control fluid and the liquid-contacting portion from being charged. If the control fluid and the liquid-contacting portion can be prevented from being charged, the increase in the potential difference between the liquid-contacting portion and the non-liquid-contacting portion inside the fluid control valve 1 can be prevented. If the increase in the potential difference can be prevented, the occurrence of dielectric breakdown of the thin film member 1222 can be prevented. If the occurrence of dielectric breakdown of the thin film member 1222 can be prevented, the occurrence of minute cracks due to dielectric breakdown can be prevented, and furthermore, the occurrence of fluid leakage and fatigue breakdown caused by the cracks can be prevented. In addition, if the charging of the control fluid can be prevented, for example, in a semiconductor manufacturing device, the charged control fluid can be prevented from contacting a wafer, thereby reducing the risk of causing defects such as developing a defective circuit pattern.
[0045] The welded portion joining the shaft member 1221 and the thin film member 1222 may be provided in an annular shape at least on the back side of the abutting portion 122b, like the welded portion 33 shown in Fig. 12. Specifically, the outer diameter D22 of the welded portion 33 may be larger than the outer diameter D12 of the annular valve seat 121d, and the inner diameter D21 may be smaller than the inner diameter D11 of the annular valve seat 121d. That is, in this embodiment, the entire boundary between the shaft member 1221 and the thin film member 1222 is the welded portion 32, which is merely an example, and represents a state in which the outer diameter D12 is maximized and the inner diameter D11 is minimized (i.e., zero).
[0046] In general, in the fluid control valve 1, the flow path area between the annular valve seat 121d and the abutment portion 122b abutting against the annular valve seat 121d is smaller than that of other portions. Therefore, the flow rate of the control fluid is faster when it flows between the annular valve seat 121d and the abutment portion 122b. Therefore, static electricity is likely to be generated when the control fluid flows between the annular valve seat 121d and the abutment portion 122b. As shown in FIG. 12, if the welded portion 33 is formed at least on the back side of the abutment portion 122b, the thin film member 1222 is joined to the shaft member 1221 with enhanced conductivity on the back side of the abutment portion 122b where static electricity is likely to be generated, which is effective in discharging static electricity.
[0047] Furthermore, forming the entire boundary between shaft member 1221 and thin film member 1222 as welded portion 32 and providing an annular welded portion 33 on the rear side of abutting portion 122b has the following effects.
[0048] In the diaphragm member according to the conventional technology (the diaphragm member disclosed in Patent Document 1), for example, as shown in FIG. 15(a), the welded portion 132 that joins the shaft member 2221 and the thin film member 2222 is located on the outer periphery side of the portion (contact portion) that contacts the annular valve seat 121d. The thin film member 2222 is generally thin, having a thickness of 0.5 mm or less, and the PFA that forms the thin film member 2222 has high gas permeability, so that gas such as nitrogen or oxygen may accumulate at the boundary portion between the shaft member 2221 and the thin film member 2222. If gas accumulates, the thin film member 2222 bulges toward the annular valve seat 121d as shown in FIG. 15(b). Since the thin film member 2222 is welded to the shaft member 2221 on the outer periphery side of the contact portion, the bulging portion of the thin film member 2222 includes the contact portion. For this reason, the position where the thin film member 2222 abuts against the annular valve seat 121d may not be the original position. If the position of the abutment portion of the thin film member 2222 that abuts against the annular valve seat 121d is shifted in this way, there is a risk that poor sealing will occur when the valve is closed, or that particles will be mixed into the control fluid due to the generation of wear powder.
[0049] If the entire boundary between the shaft member 1221 and the thin film member 1222 is the welded portion 32 as in the diaphragm member 122 in this embodiment, there is no risk of the gas that has permeated the thin film member 1222 accumulating at the boundary between the shaft member 1221 and the thin film member 1222. Also, if the welded portion 33 is provided in an annular shape at least on the back side of the abutting portion 122b as in the welded portion 33 shown in FIG. 12, even if the gas that has permeated the thin film member 1222 accumulates at the boundary between the shaft member 1221 and the thin film member 1222 and the thin film member bulges toward the annular valve seat, the abutting portion is not included in the bulging portion. Therefore, the position of the abutting portion 122b is not shifted. In this way, by preventing the positional shift of the abutting portion 122b, it is possible to reduce the risk of poor sealing when the valve is closed and of particles being mixed into the control fluid due to the generation of wear powder.
[0050] 12, in the case where a ring-shaped welded portion is provided on the back side of the abutting portion 122b, the shaft member 1221 may be provided with an air passage 1224 as shown in FIG. 13 in order to prevent gas from accumulating at the boundary between the shaft member 1221 and the thin film member 1222. The air passage 1224 extends from the inner periphery side of the welded portion 33 of the boundary between the shaft member 1221 and the thin film member 1222 to the outer periphery of the shaft member 1221. As a result, gas that has permeated the thin film member 1222 is discharged to the outside of the diaphragm member 122 through the air passage 1224.
[0051] (Operation of the fluid control valve) The operation of the fluid control valve 1 having the above-mentioned configuration will be described. The fluid control valve 1 shown in FIG. 1 is in a valve-closed state. In this state, when the operation air is supplied from the operation air supply source (not shown) to the second supply and exhaust port 112a, the operation air is supplied to the lower chamber 116b through the ventilation passage 112b. As the operation air is supplied, the pressure in the lower chamber 116b increases. Then, when the pressure received by the lower end face of the piston portion 113a exceeds the biasing force of the coil spring 114, the drive shaft 113 moves in the valve-opening direction (upward in FIG. 1) against the biasing force of the coil spring 114. Then, as the drive shaft 113 moves in the valve-opening direction, the air in the upper chamber 116a is compressed by the piston portion 113a and exhausted to the outside of the drive portion 11 through the ventilation passage 111b and the first supply and exhaust port 111a. When the drive shaft 113 moves in the valve opening direction, the diaphragm member 122 screwed to the tip of the second piston rod 113c moves in the valve opening direction. Then, when the thin film member 1222 (contact portion 122b) moves away from the annular valve seat 121d, the fluid control valve 1 is in the valve open state as shown in FIG.
[0052] When the supply of operating air to the fluid control valve 1 in the open state is stopped, the pressure of the lower chamber 116b that resists the urging force of the coil spring 114 no longer acts, and the urging force of the coil spring 114 moves the drive shaft 113 in the valve closing direction. Then, the diaphragm member 122 screwed to the tip of the second piston rod 113c also moves in the valve opening direction, and the thin film member 1222 (contact portion 122b) contacts the annular valve seat 121d. This causes the fluid control valve 1 to be in the valve closing state. At this time, the operating air filled in the lower chamber 116b is exhausted to the outside of the drive unit 11 through the ventilation passage 112b and the second supply and exhaust port 112a, and air from outside the drive unit 11 flows into the upper chamber 116a through the first supply and exhaust port 111a and the ventilation passage 111b.
[0053] (About the manufacturing method of the fluid control valve) Next, a method for manufacturing the fluid control valve 1 according to this embodiment will be described with reference to the drawings. Figures 5(a) to 5(c) are views for explaining the process of manufacturing the diaphragm member 122 by laser welding. Figure 6 is an image diagram showing the scanning state of the infrared laser 25 as viewed from the light source side during laser welding. Figure 7 is a cross-sectional view taken along line BB in Figure 6, showing the state after laser welding.
[0054] In the method of manufacturing the fluid control valve in this embodiment, the shaft member 1221 and the thin film member 1222 are joined together to obtain the diaphragm member 122 as follows.
[0055] First, as shown in Fig. 5(a), the shaft member 1221 is placed facing and in contact with the support 23. At this time, the shaft member 1221 is placed with the surface to be bonded to the thin film member 1222 facing upward. Furthermore, the thin film member 1222 is placed in surface contact with the shaft member 1221 so as to be superimposed on the shaft member 1221. At this time, the thin film member 1222 and the shaft member 1221 are placed so that their central axes are aligned.
[0056] 5(b), an infrared-transmitting solid 22 having a heat sink effect is placed in contact with the thin film member 1222 on the opposite side of the support body 23 to the stacked shaft member 1221 and thin film member 1222. Here, examples of the infrared-transmitting solid 22 include infrared crystalline materials having a thermal conductivity of 15 w / m·K or more, such as zinc selenium (ZnSe), zinc sulfide (Zns), silicon (Si), germanium (Ge), sapphire (Al2O3), gallium arsenide (GaAs), and magnesium fluoride (MgF2).
[0057] Next, as shown in FIG. 5(c), a compressive force is applied in the direction of the arrow F to bring the shaft member 1221 and the thin film member 1222 into close contact with each other, while the infrared laser 25 is irradiated from the light source 24 to the shaft member 1221 and the thin film member 1222 from the side of the infrared-transmitting solid 22. The infrared laser 25 has a wavelength of 0.37 μm to 15 μm, and is preferably a CO2 laser with a wavelength of 10.6 μm or 10.6±0.5 μm, a CO laser with a wavelength of 5.3 μm or 5.3±0.5 μm, or a semiconductor laser with a wavelength of 375 to 2000 nm. In the case of a semiconductor laser, it is preferably a YAG laser with a wavelength of 1.06 μm or 1.06±0.5 μm, a fiber laser with a wavelength of 1.07 μm or 1.07±0.5 μm, or a thulium laser with a wavelength of 2.05 μm or 2.05±0.5 μm.
[0058] The focus of the infrared laser 25 is adjusted so that the temperature distribution in the thin film member 1222 and the shaft member 1221 during irradiation with the infrared laser 25 is highest at the boundary between the thin film member 1222 and the shaft member 1221. As a result, the vicinity of the boundary between the thin film member 1222 and the shaft member 1221 melts, and the solidified portion becomes a weld mark. The welded portion 32 that joins the thin film member 1222 and the shaft member 1221 is formed by providing a plurality of annular weld marks W11-W15 in a concentric pattern.
[0059] 6, infrared laser 25 is irradiated to form welded portion 32. Irradiation of infrared laser 25 starts at start position P11. This start position P11 is located on the central axis of shaft member 1221 and thin film member 1222. When irradiation of infrared laser 25 starts, infrared laser 25 continues to be irradiated at start position P11 for a time required to form weld mark W11 forming the center of welded portion 32.
[0060] Thereafter, the infrared laser 25 scans from the start position P11 to a first scanning start point P12 located on the outer periphery side of the start position P11. Then, as shown by a first scanning line L11, the infrared laser 25 scans from the first scanning start point P12 in a clockwise circular motion around the central axis of the shaft member 1221 and the thin film member 1222. When the infrared laser 25 returns to the first scanning start point P12, a ring-shaped welding mark W12 is formed along the first scanning line L11.
[0061] Furthermore, the infrared laser 25 scans from the first scanning start point P12 to a second scanning start point P13 located on the outer periphery side of the first scanning start point P12. Then, as shown in the second scanning line L12, the infrared laser 25 scans from the second scanning start point P13 in a clockwise circular motion around the central axis of the shaft member 1221 and the thin film member 1222. When the infrared laser 25 returns to the second scanning start point P13, a ring-shaped welding mark W13 is formed along the second scanning line L12. The diameter of this welding mark W13 is larger than the diameter of the welding mark W12 formed along the first scanning line L11 by the distance from the first scanning start point P12 to the second scanning start point P13.
[0062] Furthermore, the infrared laser 25 scans from the second scanning start point P13 to a third scanning start point P14 located on the outer periphery side of the second scanning start point P13. Then, as shown in the third scanning line L13, the infrared laser 25 scans from the third scanning start point P14 in a clockwise circular motion around the central axis of the shaft member 1221 and the thin film member 1222. When the infrared laser 25 returns to the third scanning start point P14, a ring-shaped welding mark W14 is formed along the third scanning line L13. The diameter of this welding mark W14 is larger than the diameter of the welding mark W13 formed along the second scanning line L12 by the distance from the second scanning start point P13 to the third scanning start point P14.
[0063] By repeating the above, a plurality of weld marks are sequentially formed so that the diameter gradually increases from the inner circumference side to the outer circumference side in the radial direction. The scanning amount of the scanning lines adjacent in the radial direction (for example, the distance between the first scanning start point P12 and the second scanning start point P13, or the distance between the second scanning start point P13 and the third scanning start point P14) is made smaller than the diameter of the infrared laser 25. For example, if the diameter of the infrared laser 25 is 1 mm, the scanning amount is 0.8 mm. As a result, the weld marks adjacent in the radial direction are formed such that the weld mark on the outer circumference side is overlapped on the outer circumference of the weld mark on the inner circumference side (specifically, as shown in FIG. 7, the weld mark W12 and the weld mark W13 adjacent in the radial direction are formed such that the weld mark W13 on the outer circumference side is overlapped on the outer circumference of the weld mark W12 on the inner circumference side).
[0064] Then, in the outermost periphery, the infrared laser 25 scans from the final scanning start point P15 in a clockwise circular motion around the central axis of the shaft member 1221 and the thin film member 1222, as shown by the final scanning line L14. Then, when an annular welding mark W15 is formed along the final scanning line L14, the irradiation of the infrared laser 25 ends at the final scanning start point P15. This completes the joining of the shaft member 1221 and the thin film member 1222, and the diaphragm member 122 is obtained.
[0065] As described above, the welded portion 32 is formed by forming a plurality of annular weld marks W11-W15 from the inner circumference side to the outer circumference side without any gaps, so that when laser welding is performed, gas such as air at the boundary between the shaft member 1221 and the thin film member 1222 is expelled to the outer circumference side. This makes it possible to join the shaft member 1221 and the thin film member 1222 without any gaps.
[0066] In addition, since the shaft member 1221 is made of PFA with carbon black dispersed therein, the laser light absorption is improved compared to when the shaft member 1221 is made of a general fluororesin. Since the shaft member 1221 has an increased laser light absorption, when the shaft member 1221 and the thin film member 1222 are joined by laser welding, the shaft member 1221 easily absorbs laser light, and therefore the joining can be performed with a lower amount of heat than in the past. This makes it possible to reduce the range of the thin film member 1222 that is affected by heat from the infrared laser 25. Specifically, as shown in FIG. 7, the range of the thin film member 1222 that is affected by heat, that is, the range A11 where the weld marks W11-W15 are generated, is about 40% of the thickness t11 of the thin film member 1222 (in the conventional technology, the range A21 that is affected by heat of the thin film member 2222 joined to the shaft member 2221 that does not contain a carbon-based additive is about 80% of the thickness t21 of the thin film member 2222 and is wide (see FIG. 14)). In this way, if the area of the thin film member 1222 that is affected by heat can be reduced, it is possible to prevent a decrease in strength of the thin film member 1222 due to laser welding. This makes it possible to reduce the risk of fatigue failure of the thin film member 1222 due to repeated elastic deformation.
[0067] 6 is a scanning state of the infrared laser in the case where the entire boundary between shaft member 1221 and thin film member 1222 is made into welded portion 32. As shown in FIG 12, when welded portion 33 is provided only on the rear side of abutting portion 122b, welded portion 33 is formed by sequentially forming annular welding marks from the inner circumference side to the outer circumference side within the range of abutting portion 122b.
[0068] Moreover, the above-mentioned support 23 is for maintaining stable contact between the infrared-transmitting solid 22, the thin film member 1222, and the shaft member 1221 during irradiation with the infrared laser 25. Therefore, the material and shape of the support 23 may be any material as long as it has such a function. For example, it is possible to use a metal block or plate made of steel, aluminum alloy, copper alloy, or the like that is unlikely to undergo plastic deformation even under the compressive force indicated by the arrow F and has appropriate rigidity.
[0069] Furthermore, the support 23 may have a rubber buffer layer on the surface layer on the side irradiated with the infrared laser 25. When joining thermoplastic resin members such as PFA and PTFE, which are thin or have high thermal shrinkage, the contact pressure and contact area between the infrared-transmitting solid 22, the thin film member 1222, and the shaft member 1221 may be insufficient due to the surface unevenness of the thermoplastic resin member 22 itself, and defects such as voids, tears, and shrinkage may occur in the welded portion after joining. Therefore, if the support 23 has a buffer layer, the contact pressure and contact area between the infrared-transmitting solid 22, the thin film member 1222, and the shaft member 1221 can be improved, and defects such as voids, tears, and significant shrinkage can be suppressed after joining.
[0070] (Modification of the fluid control valve) As in the above-described fluid control valve 1, increasing the conductivity of the shaft member 1221 is effective in discharging static electricity, but it is more preferable to provide an earth 128 as in the fluid control valve 2 shown in Fig. 8. Regarding the fluid control valve 2, only the points that differ from the fluid control valve 1 will be described.
[0071] In the fluid control valve 2, the drive shaft 113 is formed of a conductor such as metal (for example, stainless steel). A conductive plate material 127 made of metal (for example, stainless steel) is attached to the upper surface of the first housing 111 that is in contact with the coil spring 114. A ground 128 is connected to this plate material 127 so that it can discharge to the outside of the fluid control valve 2. With the above configuration, in the fluid control valve 2, a conductive path is formed by the shaft member 1221 of the diaphragm member 122, the drive shaft 113, the coil spring 114, the plate material 127, and the ground 128. By forming a conductive path in this manner, it becomes possible to more reliably discharge static electricity generated when the control fluid passes through the flow path.
[0072] As an example of providing a ground, a configuration like that of a fluid control valve 3 shown in Fig. 9 is also considered. Regarding the fluid control valve 3, only the points different from the fluid control valve 1 will be described.
[0073] The overall shape of the drive shaft 119 used in the fluid control valve 3 is the same as the drive shaft 113 described above, but differs in that, for example, a metallic conductive member 120 is inserted inside.
[0074] The conductive member 120 has a large diameter portion 120a which forms the first piston rod 119b of the drive shaft 119. A disk portion 120b which forms the upper end surface of the piston portion 119a of the drive shaft 119 is formed at the lower end of the large diameter portion 120a. The lower end of the coil spring 114 abuts against this disk portion 120b. Furthermore, a small diameter portion 120c which is smaller in diameter than the large diameter portion 120a and is inserted into the inside of the drive shaft 119 extends from the lower end surface of the large diameter portion 120a. The tip of the small diameter portion 120c protrudes from the tip of the second piston rod 119c of the drive shaft 119 and is connected to the shaft member 1221.
[0075] The fluid control valve 3 is similar to the above-described fluid control valve 2 in that it includes a plate material 127 and that the plate material 127 is connected to an earth 128. With the above-described configuration, in the fluid control valve 3, a conductive path is formed by the shaft member 1221, the conductive member 120, the coil spring 114, the plate material 127, and the earth 128. By forming a conductive path in this manner, it becomes possible to more reliably discharge static electricity that is generated when the control fluid passes through the flow path.
[0076] (Modification of the diaphragm member) As a modified example of the diaphragm member, a diaphragm member 124 shown in FIG. 10 will be described only with respect to the points different from the above-mentioned diaphragm member 122.
[0077] The thin film member 1223 constituting the diaphragm member 124 is formed in two layers. Of the two layers, the first layer 1223a on the side of the annular valve seat 121d is a layer formed of PFA like the above-mentioned thin film member 1222, and has the same thickness as the thin film member 1222. Of the two layers, the second layer 1223b on the side facing the shaft member 1221 is formed of PFA with carbon black dispersed therein. That is, the second layer 1223b is a layer with enhanced conductivity. The carbon black content is preferably 1.5% by weight or more and 5% by weight or less, and more preferably 3% by weight or more and 4% by weight or less. The content in this embodiment is about 3.5% by weight. The thickness of the second layer 1223b is about 0.02 mm. Note that this thickness is merely an example, and a thickness that does not inhibit the elastic deformation of the thin film member 1222 is appropriately selected from the range of, for example, 0.01 to 0.1 mm. The first layer 1223a and the second layer 1223b may be joined by two-color molding, or the first layer 1223a and the second layer 1223b may be molded separately and then joined by compression press molding.
[0078] Since the thin film member 1223 has the above-mentioned configuration, the second layer 1223b having enhanced conductivity is welded to the shaft member 1221 having enhanced conductivity in the thin film member 1223. This makes it possible to more reliably discharge static electricity generated by the passage of the control fluid through the flow path.
[0079] In addition, since carbon black is dispersed in the second layer 1223b, the laser light absorption is enhanced. Therefore, since the second layer 1223b absorbs the laser light together with the shaft member 1221, when the shaft member 1221 and the thin film member 1222 are joined by laser welding, the joining can be performed with a lower amount of heat than in the past, and the area of the thin film member 1223 that is affected by the heat can be made smaller. The laser welding process for obtaining the diaphragm member 124 is the same as the process shown in FIG. 5.
[0080] When the diaphragm member 124 is used in a fluid control valve, it is desirable to provide a ground 126 as in the fluid control valve 4 shown in Fig. 11. Regarding the fluid control valve 4, only the points different from the fluid control valve 1 will be described.
[0081] The fluid control valve 4 is provided with a conductive member 125 made of a metal such as stainless steel at the end on the valve body 121 side (the lower end in FIG. 11). This conductive member 125 is positioned so as to come into contact with the second layer 1223b when the second housing 112 and the valve body 121 hold the thin film member 1223 from above and below. A ground 126 is connected to this conductive member 125.
[0082] With the above configuration, the fluid control valve 4 has a conductive path formed by the second layer 1223b of the diaphragm member 124, the conductive member 125, and the earth 126. By forming the conductive path in this way, it is possible to more reliably discharge static electricity generated by the passage of the control fluid through the flow path. The second layer 1223b may be formed of PFA in which carbon nanotubes are dispersed. In this case, the content of carbon nanotubes is preferably 0.01% by weight or more and 0.1% by weight or less, and the content in this embodiment is about 0.02% by weight. The configuration of the fluid control valve 4 is merely an example, and in the configurations of the fluid control valves 1, 2, and 3 described above, the diaphragm member 122 may be replaced with the diaphragm member 124.
[0083] (Materials of shaft parts) In all of the above embodiments, the shaft member 1221 is described as being made of PFA with carbon black dispersed therein, but it may be made of PFA with carbon nanotubes dispersed therein. The carbon nanotube content is preferably 0.01% by weight or more and 0.1% by weight or less, and the content in this embodiment is about 0.02% by weight.
[0084] Furthermore, the shaft member 1221 is not limited to PFA, and may be formed of PTFE (polytetrafluoroethylene) dispersed with carbon-based additives such as carbon nanotubes, carbon black, etc. Although the joining strength by laser welding is superior when the same materials (PFA) are joined together, PTFE has the advantage of being highly resistant to chemicals.
[0085] As described above, according to the fluid control valve and the manufacturing method of the fluid control valve of the present embodiment, (1) in the fluid control valves 1, 2, 3, and 4 including a flow path (for example, a series of flow paths formed by communicating the input flow path 121a and the output flow path 121b) through which a control fluid (for example, a chemical liquid) flows, an annular valve seat 121d provided on the flow path, diaphragm members 122, 124 that control the flow of the control fluid by abutting against and separating from the annular valve seat 121d, and drive shafts 113, 119 that are arranged coaxially with the annular valve seat 121d and drive the diaphragm members 122, 124 in the abutment and separation directions, the shaft member 1221 being connected to the end of the drive shaft 113, 119 on the side of the annular valve seat 121d; thin film members 1222, 1223 made of perfluoroalkoxyalkane and positioned in face-to-face contact with the end face of the shaft member 1221 opposite the end connected to the drive shaft 113, 119; and laser-welded welded portions 32, 33 that join the shaft member 1221 and the thin film members 1222, 1223 at the boundary between the shaft member 1221 and the thin film members 1222, 1223, the shaft member 1221 being made of a fluororesin (e.g., PFA or PTFE) having a carbon-based additive dispersed therein.
[0086] (5) In a method for manufacturing a fluid control valve, the fluid control valves 1, 2, 3, and 4 are provided with a flow path (for example, a series of flow paths formed by connecting an input flow path 121a and an output flow path 121b) through which a control fluid (for example, a chemical liquid) flows, an annular valve seat 121d provided on the flow path, diaphragm members 122, 124 that control the flow of the control fluid by abutting against and separating from the annular valve seat 121d, and a drive shaft 113, 119 that is arranged coaxially with the annular valve seat 121d and drives the diaphragm members 122, 124 in the abutment and separation direction, the shaft member 1221 being made of a fluororesin (e.g., PFA or PTFE) containing a carbon-based additive; and thin film members 1222, 1223 made of perfluoroalkoxyalkane and positioned in face-to-face contact with the end face of the shaft member 1221 opposite the end face connected to the drive shafts 113, 119, thereby joining the thin film members 1222, 1223 by laser welding to form welded portions 32, 33 at the boundaries between the shaft member 1221 and the thin film members 1222, 1223 to obtain diaphragm members 122, 124; and the shaft member 1221 being made of a fluororesin (e.g., PFA or PTFE) containing a carbon-based additive.
[0087] According to the fluid control valves 1, 2, 3, and 4 described in (1) or the manufacturing method for a fluid control valve described in (5), the shaft member 1221 is made of a fluororesin having a carbon-based additive dispersed therein, and therefore has higher conductivity than a shaft member made of a general fluororesin. This allows static electricity generated by the passage of the control fluid through the flow path to be discharged, and makes it possible to prevent the control fluid and the liquid-contacting parts from being charged.
[0088] If the control fluid and the wetted parts can be prevented from being charged, the increase in the potential difference between the wetted parts and non-wetted parts inside the fluid control valves 1, 2, 3, 4 can be prevented. If the increase in the potential difference can be prevented, the occurrence of dielectric breakdown of the thin film members 1222, 1223 can be prevented. If the occurrence of dielectric breakdown of the thin film members 1222, 1223 can be prevented, the occurrence of microcracks due to dielectric breakdown can be prevented, and further, the occurrence of fluid leakage and fatigue breakdown caused by the cracks can be prevented. In addition, if the control fluid can be prevented from being charged, for example, in a semiconductor manufacturing device, it is possible to prevent the charged control fluid from coming into contact with a wafer, thereby reducing the risk of developing a defective circuit pattern or other malfunctions.
[0089] In addition, according to the fluid control valves 1, 2, 3, and 4 described in (1) or the manufacturing method of the fluid control valve described in (5), the shaft member 1221 is made of fluororesin with a carbon-based additive dispersed therein, and therefore has a higher laser light absorption than when made of a general fluororesin. Since the laser light absorption of the shaft member 1221 is increased, when the shaft member 1221 and the thin film members 1222 and 1223 are joined by laser welding, the shaft member 1221 easily absorbs laser light, so that joining can be performed with a lower amount of heat than before, and the range A11 of the thin film members 1222 and 1223 that is affected by heat can be made smaller than before. If the range A11 of the thin film members 1222 and 1223 that is affected by heat can be made smaller, it is possible to prevent the strength of the thin film members 1222 and 1223 from decreasing due to laser welding. This can reduce the risk of fatigue failure of the thin film members 1222 and 1223 due to repeated elastic deformation.
[0090] (2) In the fluid control valves 1, 2, 3, and 4 described in (1), the thin film members 1222 and 1223 are characterized in that they have a contact portion 122b that abuts against the annular valve seat 121d on the surface opposite the shaft member 1221, and the welded portions 32 and 33 are formed at least on the back side of the contact portion 122b.
[0091] (6) In the method for manufacturing a fluid control valve described in (5), the thin film members 1222, 1223 are characterized in that they have an abutment portion 122b that abuts against the annular valve seat 121d on the surface opposite the shaft member 1221, and the welded portions 32, 33 are formed at least on the back side of the abutment portion 122b.
[0092] In general, in a fluid control valve, the flow passage area between the annular valve seat and the abutment portion that abuts against the annular valve seat is smaller than the other portions. Therefore, the flow speed of the control fluid is fast when it flows between the annular valve seat and the abutment portion. Therefore, static electricity is easily generated when the control fluid flows between the annular valve seat and the abutment portion.
[0093] According to the fluid control valves 1, 2, 3, and 4 described in (2) or the manufacturing method of a fluid control valve described in (6), the welded parts 32 and 33 are formed on the back side of the contact part 122b. That is, the thin film members 1222 and 1223 are joined to the shaft member 1221 with enhanced conductivity on the back side of the contact part 122b where static electricity is likely to be generated, so that discharge can be performed more reliably.
[0094] (3) In the fluid control valve 1, 2, 3, 4 described in (1) or (2), the thin film member 1223 is characterized in that it has a layer (second layer 1223b) containing a carbon-based additive on the side facing the shaft member 1221.
[0095] (7) In the method for manufacturing a fluid control valve described in (5) or (6), the thin film member 1223 is characterized in that it has a layer (second layer 1223b) containing a carbon-based additive on the side facing the shaft member 1221.
[0096] According to the fluid control valves 1, 2, 3, and 4 described in (3) or the manufacturing method for a fluid control valve described in (7), the thin film member 1223 includes a layer (second layer 1223b) containing a carbon-based additive and having enhanced electrical conductivity on the side facing the shaft member 1221. That is, the thin film member 1223 has the layer (second layer 1223b) having enhanced electrical conductivity joined to the shaft member 1221 having enhanced electrical conductivity. This makes it possible to more reliably discharge static electricity generated by the passage of the control fluid through the flow path.
[0097] Moreover, according to the fluid control valves 1, 2, 3, and 4 described in (3) or the manufacturing method of the fluid control valve described in (7), the thin film member 1223 includes a layer (second layer 1223b) containing a carbon-based additive and having enhanced laser light absorbency on the side facing the shaft member 1221. That is, the thin film member 1223 has a layer with enhanced laser light absorbency bonded to the shaft member 1221 with enhanced laser light absorbency. Since the layer (second layer 1223b) of the shaft member 1221 and the thin film member 1223 facing the shaft member 1221 easily absorbs laser light, when the shaft member 1221 and the thin film member 1223 are bonded by laser welding, bonding can be performed with a lower amount of heat than in the past, and the range of the thin film member 1223 that is affected by heat can be made smaller.
[0098] (4) In the flow control valve 1, 2, 3, or 4 described in any one of (1) to (3), the carbon-based additive is preferably, for example, carbon black or carbon nanotubes.
[0099] (8) In the method for producing a flow control valve according to any one of (5) to (7), the carbon-based additive is carbon black or carbon nanotubes.
[0100] When carbon black is used, the content is preferably 1.5% by weight or more and 5% by weight or less, and more preferably 3% by weight or more and 4% by weight or less. If the content is less than 1.5% by weight, sufficient laser light absorption and electrical conductivity cannot be obtained. Also, the higher the content, the higher the laser light absorption and electrical conductivity can be, but if the content exceeds 5% by weight, there is a concern that the material strength may decrease.
[0101] When carbon nanotubes are used, the content is preferably 0.01% by weight or more and 0.1% by weight or less. If the content is less than 0.01% by weight, sufficient laser light absorption and electrical conductivity cannot be obtained. Also, the higher the content, the higher the laser light absorption and electrical conductivity can be, but if the content exceeds 1% by weight, there is a concern that the material strength may decrease.
[0102] The above-mentioned embodiment is merely an example, and does not limit the present invention in any way. Therefore, the present invention can be improved and modified in various ways without departing from the scope of the present invention. For example, the drive system of the fluid control valve 1 has been described as an air-operated type, but the drive system is not limited to this. Also, the fluid control valve 1 has been described as a normally closed type, but it may be a normally open type. [Explanation of symbols]
[0103] 1. Fluid control valve 32 Welded area 113 Drive shaft 121d Annular valve seat 122 Diaphragm member 1221 Shaft member 1222 Thin film materials
Claims
1. A fluid control valve comprising: a flow path through which a control fluid flows; an annular valve seat provided in the flow path; a diaphragm member that controls the flow of the control fluid by moving toward and away from the annular valve seat; and a drive shaft that is coaxially arranged with the annular valve seat and drives the diaphragm member in the direction of moving toward and away from the annular valve seat, The diaphragm member is a shaft member coupled to an end of the drive shaft on the side of the annular valve seat; a thin film member made of perfluoroalkoxyalkane and positioned in surface contact with an end face of the shaft member opposite to the end face coupled to the drive shaft; a welded portion formed by laser welding at a boundary between the shaft member and the thin film member, the welded portion joining the shaft member and the thin film member; To have The shaft member is made of a fluororesin having a carbon-based additive dispersed therein; the shaft member absorbs the laser light when the laser welding is performed, thereby making the area in the thin film member where a weld mark is generated by the laser welding smaller than half the thickness of the thin film member, thereby preventing a decrease in strength of the thin film member; A fluid control valve comprising:
2. 2. The fluid control valve according to claim 1, the thin film member has an abutment portion that abuts against the annular valve seat on a surface opposite to the shaft member; The welded portion is formed at least on a rear side of the abutting portion; A fluid control valve comprising:
3. 3. The fluid control valve according to claim 1, the thin film member has a layer containing the carbon-based additive on a side facing the shaft member; A fluid control valve comprising:
4. 3. The fluid control valve according to claim 1, The carbon-based additive is carbon black or carbon nanotubes; A fluid control valve comprising:
5. A method for manufacturing a fluid control valve comprising: a flow path through which a control fluid flows; an annular valve seat provided on the flow path; a diaphragm member that controls a flow of the control fluid by coming into contact with and moving away from the annular valve seat; and a drive shaft that is coaxially arranged with the annular valve seat and drives the diaphragm member in the direction of coming into contact with and moving away from the annular valve seat, a shaft member coupled to an end of the drive shaft on the side of the annular valve seat; a thin film member made of perfluoroalkoxyalkane and positioned in surface contact with an end surface of the shaft member opposite to the end surface coupled to the drive shaft; a step of forming a welded portion at a boundary between the shaft member and the thin film member by laser welding to join them and obtain the diaphragm member; The shaft member is made of a fluororesin containing a carbon-based additive; the shaft member absorbs the laser light when the laser welding is performed, thereby making the area in the thin film member where a weld mark is generated by the laser welding smaller than half the thickness of the thin film member, thereby preventing a decrease in strength of the thin film member; A method for manufacturing a fluid control valve comprising the steps of:
6. 6. The method for manufacturing a fluid control valve according to claim 5, the thin film member has an abutment portion that abuts against the annular valve seat on a surface opposite to the shaft member; The welded portion is formed at least on a rear side of the abutting portion; A method for manufacturing a fluid control valve comprising the steps of:
7. 7. The method for manufacturing a fluid control valve according to claim 5 or 6, the thin film member has a layer containing the carbon-based additive on a side facing the shaft member; A method for manufacturing a fluid control valve comprising the steps of:
8. 7. The method for manufacturing a fluid control valve according to claim 5 or 6, The carbon-based additive is carbon black or carbon nanotubes; A method for manufacturing a fluid control valve comprising the steps of:
Citation Information
Patent Citations
Method for joining pipe-shaped article
JP2004090628A
Laser welding method of resin members
JP2009143149A
Diaphragm valve
JP2010121689A
Diaphragm member, and diaphragm valve using diaphragm member
JP2020026846A
Diaphragm valve
JP2022029522A